2011
DOI: 10.1017/s1461145711001763
|View full text |Cite
|
Sign up to set email alerts
|

Children under stress – COMT genotype and stressful life events predict cortisol increase in an acute social stress paradigm

Abstract: Dopamine and norepinephrine are key regulators of cognitive and affective processes. The enzyme catechol-O-methyltransferase (COMT) catabolizes catecholamines and the COMT Val158Met polymorphism has been linked to several neuropsychiatric variables. Additionally, stressful life events (SLEs) contribute substantially to affective processes. We used the stress-induced activation of the hypothalamic-pituitary-adrenal axis to investigate the effects of COMT and SLEs on the cortisol response in 119 healthy children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 89 publications
(120 reference statements)
2
40
0
2
Order By: Relevance
“…However, this benefit comes with a trade-off of disadvantageous emotion-related information processing likely because of increased subcortical tonic and increased cortical phasic dopaminergic signaling (Bilder et al, 2004;Mier et al, 2010). Correspondingly, the Met allele has been associated with stress-related phenotypes, such as exaggerated limbic response to unpleasant stimuli (Smolka et al, 2005(Smolka et al, , 2007, HPA axis hyperreactivity (Armbruster et al, 2012), and increased pain sensitivity (Zubieta et al, 2003). This balance of costs and benefits suggests that each allele can be advantageous depending on the environmental context ("warrior vs worrier" model) in line with our data (Goldman et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this benefit comes with a trade-off of disadvantageous emotion-related information processing likely because of increased subcortical tonic and increased cortical phasic dopaminergic signaling (Bilder et al, 2004;Mier et al, 2010). Correspondingly, the Met allele has been associated with stress-related phenotypes, such as exaggerated limbic response to unpleasant stimuli (Smolka et al, 2005(Smolka et al, , 2007, HPA axis hyperreactivity (Armbruster et al, 2012), and increased pain sensitivity (Zubieta et al, 2003). This balance of costs and benefits suggests that each allele can be advantageous depending on the environmental context ("warrior vs worrier" model) in line with our data (Goldman et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanisms of how dopamine affects hippocampal volume are still obscure but may involve alterations of the dopamine-modulated stress response that translate to changes of HPA axis function (Armbruster et al, 2012;Hernaus et al, 2013). Moreover, given the high hippocampal COMT expression, also direct effects on local dopamine signaling and hippocampal plasticity may be possible (Matsumoto et al, 2003;Lisman et al, 2011;Laatikainen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, another possibility is that Val carriers exhibit abnormal reward processing as found in a neuroimaging study (Camara et al, 2010). COMT is significantly associated with various psychiatric disorders (e.g., Hosak, 2007) as well as levels of cortisol response (e.g., cortisol stress reactivity in Armburster et al, 2012, Jabbi et al, 2007; total morning cortisol output in Walder et al, 2010). …”
Section: Cortisol Reactivity To Stress Stability and Associations Wmentioning
confidence: 99%
“…Children carrying the Met allele showed a higher cortisol response to stress. However, children who had more stressful life events showed a smaller increase in cortisol, implying that they might be more resilient (Armbruster et al, 2012). This study demonstrated differential effects of genetic and environmental factors on reaction to stress.…”
Section: Noradrenergic and Dopaminergic Systemsmentioning
confidence: 63%